Istikhdām Kitāb “al-Tațbīq al-Nahwī wa al-Șarfī” bi al-Ṭarīqah al-Qiyāsiyyah fi Ṭārqiyyah Sayṭarah al-Ṭalabah ‘Ala al-Jumlah al-Ismiyyah bi Ma’had Dār al-Ulūm Bandā ‘Atsyīh Indonisiā - kasyful anwar (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Every “kalam” in Arabic is a sentence “jumlah”. The ability of student to express something in their mind’s, or their heart’s, or convey the idea, or giving information to other, or reading comprehension, or daring to speak with Arabs, or interaction with other is affected by understanding of the “jumlah”. The problem which experienced by student in class Va in Darul Ulum Islamic Boarding School is understanding of “jumlah ismiyah” was still little bit. Therefore, expected to teachers who teach nahwu’s lesson to use a method or a correspond’s book. And name of the book is al-Ṭabīq al-Nuhawil wa al-Șarfi. The aim of this research is to know effectiveness al-Ṭabīq al-Nuhawil wa al-Șarfi book to improve student’s ability in understanding “jumlah ismiyah”. The method used in this research is Quasi Experiment. This study conducted in class five Darul Ulum Islamic boarding school Banda Aceh, Indonesia. The total sample was twenty eight students of class five A. This research found that the use at-Tathbiq an-Nahwi wa as-Sharfi textbook to improve students’ ability in the understanding “jumlah ismiyah” is very effective.